Exploring undergraduate students’ productive struggles in a quantitative literacy course: Implications for the development of tutoring - Mhakure, D.; Jaftha, J.; Rughubar-Reddy, S.; Manzini, M. (South African Journal of Higher Education, 2019)
The present study explores undergraduate students’ productive struggles in a Quantitative Literacy (QL) course, when doing exercises on the statistical concept of confidence intervals (CIs) within the context of odds ratios (ORs), embedded in everyday authentic contexts. The research methodology employed in this study is lesson study, in which tutors and researchers work together to plan the research tutorial, observe and teach it, and reflect on the instruction in general within the research tutorial. Data for this study comprises video- and audio- recorded transcriptions of the observation and teaching, and reflections of tutors on research tutorials. In addition, samples of students’ work and their achievements in assessments were analysed. Results from the study showed that the students’ struggles were initiated when their prior knowledge was not sufficient for them to understand the concept of CIs in relation to ORs. The results also highlight some of the ways in which tutors can notice and address students’ productive struggles during tutorials. Future researchers should focus on identifying which instructional approaches can promote and support prolific productive struggles for students during tutoring.